Triple Burden of Malnutrition and Nutrition Literacy Among Female Senior High School Students: A Systematic Review - Harahap, Huntari; Asyhar, Rayandra; Wicaksana, Ervan Johan; Marzal, Jefri; Rey Ugsang Acob, Joel (Jurnal Kesmas Jambi, 2026)
Indonesia is experiencing a triple burden of malnutrition (TBM), characterized by the coexistence of undernutrition (stunting, chronic energy deficiency/CED), overnutrition (overweight/obesity), and micronutrient deficiencies, particularly iron-deficiency anemia among adolescents. Female senior high school students represent a critical target group for preconception stunting prevention; however, evidence on TBM and nutrition literacy in this population has not been systematically synthesised. This systematic review examines the prevalence of TBM and the effectiveness of nutrition literacy interventions among female senior high school students in preventing preconception stunting during 2021–2025. The review adhered to PRISMA 2020 guidelines and employed the PICOS framework. Literature searches were conducted in PubMed, ScienceDirect, Scopus, Google Scholar, Garuda, and SINTA for articles published between January 2021 and October 2025. Study quality was appraised using Joanna Briggs Institute tools, the strength of evidence was assessed using the GRADE approach, and narrative-thematic synthesis was performed in accordance with SWiM guidelines. Of 1,247 screened articles, 28 met the inclusion criteria. Among Indonesian female senior high school students, pooled prevalence ranges were stunting 17.9–25%, CED 8.7–36.3%, anemia 23.9–42.1%, and overweight/obesity 9.5–18.6%. Nutrition literacy was insufficient to moderate in 46–68% of respondents. Interventions using video, booklets, digital media, and peer education consistently improved knowledge scores (Δ = 12–35 points), although their effects on behavior and nutritional status were limited. The GRADE assessment indicated moderate certainty for nutrition literacy and education-related determinants and low certainty for single-component interventions. The prevalence of TBM among Indonesian female senior high school students requires urgent attention; multicomponent interventions integrated with iron-folate supplementation and cross-sectoral policies are recommended.